Experimental study of boiling heat transfer in smooth/micro-fin tubes of four refrigerants. (July 2016) - Jiang, G.B.; Tan, J.T.; Nian, Q.X.; Tang, S.C.; Tao, W.Q.
Highlights: Boiling test data are got for developing a generally-accepted correlation. The working fluids include R22 and its alternatives. The heat transfer data in micro-fin tubes are conducted. The pressure drop data in micro-fin tubes are conducted. The efficiency index data in micro-fin tubes are conducted. Abstract: An experimental investigation of boiling characteristics in a horizontal smooth and micro-fin tube with 9.52 mm outside diameter and 1 m length was conducted. The refrigerants tested were R22, R134a, R407C and R410A while vapour quality ranges from 0.1 to 0.9, mass flux 50, 250, 450 kg m −2  s −1 and heat flux of 5, 12.5, 20 kW m −2 . The saturation temperature is 5 °C. For the smooth tube, the average heat transfer coefficients of R134a, R407C and R410A are 110.9%, 78.0% and 125.2% of those of R22 in test conditions respectively. For the micro-fin tube, the average heat transfer coefficients of R22, R134a, R407C and R410A are 1.86, 1.80, 1.69 and 1.78 times higher than those of the smooth tube. The pressure drop of R22, R407C and R410A for the smooth tube is similar to each other while the pressure drop of R134a is 1.7 times higher. The average pressure drop of R22, R134a, R407C and R410A for the micro-fin tube is 1.42, 1.30, 1.45 and 1.40 times higher when compared with that for the smooth one. Considering the effect of heat transfer enhancement and pressure drop augment, the efficiency index η 1 which values the thermo-hydraulic performance at identical flow rate of R22, R134a, R407C and R410A in the micro-fin tube used is 1.31, 1.38, 1.17 and 1.27 respectively compared with the smooth tube.